Role of height of an individual and low lying pubic tubercle as risk factors of inguinal hernia: case controlled study - Bhandary, Disha; Amin, Rachan; Shetty, Ranjith (International Journal of Research in Medical Sciences, 2023)
Background: Hernia is defined as abnormal protrusion of whole or a part of a viscus through the wall that contains it. Among all external abdominal hernias, inguinal hernia is one most typically encountered. Many factors are responsible for the formation of hernia. We intended to study the risk of inguinal hernia in low lying pubic tubercle. Methods: The study was conducted on patients in AJIMS, India. It is a case-control study with 80 cases and 80 control meeting inclusion criteria, in all patients, following parameters SS line, ST line, height, weight was recorded and evaluated. Results: The average SS value for case which was much above the average in control.ST value was higher case group than control group, and p<0.0001 which was significant. when it comes to the mean of (SS/ST ratio)/height was higher in the case group than control group. Results developed show majority of the subjects with a low-lying pubic tubercle were inguinal hernia patients. Conclusions: Based on my study, interspinal distance (SS line) and pubo-spinal distance (ST line) are more in cases compared to control. Configuration of bony pelvis seems to be a major contributing factor in determining the risk of development of inguinal hernia as evidenced by the variations in ST length. This low-lying pubic tubercle is very important before selecting the patient for any surgical correction. So, the proper demonstration of anatomy of inguinal region is very important before selecting the surgical technique.